Permainan bola berantai untuk peningkatan hasil belajar bola voli pada siswa kelas IV SDN 12 Api – Api Kecamatan Bayang Kabupaten Pesisir Selatan - Kasmirman Kasmirman (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
The purpose of this research is to know the learning result of passing through the volley ball through game with the ball of the chain at the fourth-grade student of SDN 12 Api - Api Kec. Bayang. The sample of research is 24 people. The type of research used is classroom action research (PTK). The results showed an increase in student learning outcomes.